R&D study on materials adjustment for Basic Listening course - Maria Dwi Winarni; Yasmin Farani (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
Due to the last two year Covid-19 Pandemic, the teaching learning activities were globally switched, from offline to online learning. This happened at University of Merdeka Malang, too. One of the researchers, who taught Basic Listening course at Diploma Three English Program, had to change language laboratory activities into synchronous and asynchronous activities. Inevitably, it was resulted in the teaching materials as well. The objective of this RD study is to propose the use of Internet technology through selected videos in the YouTube Channel to partially adjust the existing teaching materials in the above mentioned course. As the primary instruments, the researchers adapted the framework of Graves’ materials development and used questionnaires as the secondary instruments. Graves’ framework consists of seven components of course development processes, however, the researchers did not use or apply them all (only Steps 4, 5 and 6) since they just made partial adjustment to the existing materials usually used during the offline class. The finalproducts of this study were in the form of softcopy files given to the students as handouts.    DOI: 10.26905/enjourme.v7i2.8738